2020
DOI: 10.1002/ijc.32978
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure to air pollution and risk of non‐Hodgkin lymphoma in Denmark: A population‐based case–control study

Abstract: There is limited evidence regarding a possible association between exposure to ambient air pollutants and the risk of non‐Hodgkin lymphoma (NHL). Previous epidemiological studies have relied on crude estimations for air pollution exposure and/or small numbers of NHL cases. The objective of our study was to analyze this association based on air pollution modeled at the address level and NHL cases identified from the nationwide Danish Cancer Registry. We identified 20,874 incident NHL cases diagnosed between 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A case‐control study that included 1064 total incident leukemia cases and 5039 controls across Canada observed no clear association with PM 2.5 overall or when examining chronic lymphocytic leukemia specifically 123 . Studies in Denmark have reported no clear associations of ambient air pollutant exposure and incident NHL, 109,124 although, in one study, significant adverse associations of primary carbonaceous and secondary organic aerosols were observed 125 . A Danish case‐control study of 1967 incident leukemia cases and 3381 controls reported significant adverse associations of ambient NO 2 (OR per 10 µg/m 3 , 1.31; 95% CI, 1.02‐1.68) and NO x (OR per 20 µg/m 3 , 1.20; 95% CI, 1.04‐1.38) and incident acute myeloid leukemia (AML) 126 …”
Section: Epidemiological Studies Of Outdoor Air Pollution and Other Tmentioning
confidence: 99%
“…A case‐control study that included 1064 total incident leukemia cases and 5039 controls across Canada observed no clear association with PM 2.5 overall or when examining chronic lymphocytic leukemia specifically 123 . Studies in Denmark have reported no clear associations of ambient air pollutant exposure and incident NHL, 109,124 although, in one study, significant adverse associations of primary carbonaceous and secondary organic aerosols were observed 125 . A Danish case‐control study of 1967 incident leukemia cases and 3381 controls reported significant adverse associations of ambient NO 2 (OR per 10 µg/m 3 , 1.31; 95% CI, 1.02‐1.68) and NO x (OR per 20 µg/m 3 , 1.20; 95% CI, 1.04‐1.38) and incident acute myeloid leukemia (AML) 126 …”
Section: Epidemiological Studies Of Outdoor Air Pollution and Other Tmentioning
confidence: 99%
“…The study used case-control design and the authors suggested selection bias as a possible explanation. Two large population-based studies from Denmark reported no association between outdoor air pollution and the risk of adult Hodgkin and non-Hodgkin lymphoma (Taj et al, 2021a;Taj et al, 2020a). The Danish study investigating non-Hodgkin lymphoma reported a higher…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study in Germany showed that long-term exposure to air pollution was associated with the incidence of Monoclonal Gammopathy of Undetermined Significance (MGUS), a plasma cell disorder which has been associated with non-Hodgkin lymphomas (Orban et al, 2017). Various other studies of general populations have found no or a decrease in risk among individuals after exposure to air pollution at the residential address in Denmark (Taj et al, 2021a;Taj et al, 2020b) or to industrial waste gas emissions in China (Cong, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 108 , 109 The American Cancer Society Cancer Prevention Study II (ACS CPS-II) initially reported that ambient exposures to fine particulate matter (PM 2.5 ), nitrogen dioxide (NO 2 ), or ozone (O 3 ) were not associated with NHL risk. 110 In addition, two studies based on the Danish Cancer Registry also found no association between NHL and PM 2.5 , NO 2 , or O 3 111 , 112 . However, several recent studies observed an increased NHL risk associated with ambient air pollution.…”
Section: Air Pollutionmentioning
confidence: 97%